IDENTIFICATION, INDIVIDUALIZATION AND UNIQUENESS: WHAT IS THE DIFFERENCE (International journal of artificial intelligence, 2024)
Criminologists and many forensic trace evidence specialists distinguish between identification and individualization, but they do not clearly distinguish between individualization and uniqueness. This article explains these terms and discusses the relationships between identification, individualization, and uniqueness of forensic evidence.